Synergistic iron enhanced aerogel and peracetic acid for degradation of emerging organic contaminants - Lili Jin; Tong Li; Xiaoya Fang; Zhao Xue; Hui Huang; Hongqiang Ren (npj Clean Water)
Abstract In response to the urgent need for efficient degradation of emerging organic contaminants, this study has developed a novel catalytic system based on an original Fe-doped aerogel catalyst (FeCAS) and its carbonization-enhanced variant (FeCAS-400), designed to improve the activation performance of peracetic acid (PAA). The FeCAS/PAA achieves a remarkable 96.1% degradation of sulfamethoxazole (SMX) without external energy input, while the FeCAS-400/PAA further elevates the SMX removal rate to 98.4% (k obs = 0.326 min−¹) and demonstrates effectiveness across a broad pH range of 3–11. Theoretical calculations reveal that carbonization enhances electron transfer between iron–carbon substrates, which contributes to improved catalytic performance. The system also exhibits versatility in removing a wide range of prevalent contaminants and proves effective in real water matrices. This synergistic approach, combining aerogels with metal–carbon electron transfer, holds promise for an extension to other advanced oxidation processes, contributing to the assurance of water quality safety and sustainability.